Local wisdom of the fisherman community (Case study of North Galesong coastal community mutual cooperation, Takalar Regency) - Yudid Srywahyuni Silomba; Rahmat Muhammad; Muhammad Sabiq; Hasbi Hasbi (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
This study examines the traditional local wisdom of the fishing community, North Galesong. This study aims to describe the position of local wisdom in the midst of modernity. This study uses a case study qualitative approach. Data obtained from primary and secondary sources. The data collection technique is done by interview, observation and documentation. The results of this study indicate that the local wisdom of mutual cooperation in the withdrawal of fishing boats in North Galesong has faded since the entry of modernity contamination. The change in the towing of the ship is based on rational considerations related to the effectiveness of work and respect for other community activities. The towing of ships carried out in mutual cooperation is more costly and time consuming. Towing ships using modern tools such as excavators is more efficient.